Bone mineral loss in middle and old age : mechanisms and treatments - Stini, William A. (Array, 1990)
The mechanisms of bone mineral loss after menopause and in old age involve both bone resorption and bone formation. Humoral and local factors affect both processes. As the list of potential treatments for osteoporosis grows, it is evident that the apparently contradictory results reported by different investigators reflect the occurrence of unanticipated alterations in conditions outside the experimental protocol. Results of a limited trial with a nonsteroidal anti-inflammatory medication known to be a prostaglandin inhibitor indicate that such medications may play a useful role in slowing the rate of bone resorption, particularly in the trabecular envelope